Fabrication of chitosan membrane : The effects of different chitosan compositions on membrane performance in treating oily wastewater - Nurulhuda, Md. Noh (2008)
In this research four fabricated chitosan membrane was produced with different chitosan compositions. The membrane produced using the solvent casting method. All the fabricated membrane then was characterized using the scanning electron microscope (SEM) and tested using the different molecular weight (MWCO) to determine the pore size. The result of SEM shows that the fabricated membranes have an asymmetric membrane. The MWCO of the fabricated membrane is 1000 where it crosses the 90 percent the rejection rate. And lastly, the method of oil swelling was used to determine the favorable fabricated membrane to treat the oily wastewater. As a conclusion, the CHI-4 was the one favorable membrane to solve the oily problem with degree of oil swelling up to 227.80 % and also this fabricated membrane has a higher degree of oil swelling compare to the others membrane.